La mise en place du système monétaire européen - Lelart, Michel (L'Actualité économique, 1979)
The author of this paper features the main events that led to the creation of a European monetary system. In the first part, the three stages of the European monetary construction are recalled. In the second part, the author analyses the agreement that occurred on December 5, 1978.